Case 3806: Paranemastoma superbum Redikortsev, 1936 (Arachnida, Opiliones, Nemastomatidae): proposed conservation of usage of the specific name by giving it precedence over Nemastoma supersum Roewer, 1951 - Kury, Adriano B (Bulletin of Zoological Nomenclature)
Noticed in BZN 76 (30 Aug 2019): 98.